2007
DOI: 10.1177/000313480707301030
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Lymphoma: A Rare and Morbid Tumor

Abstract: We conducted a retrospective tumor registry review of a 36-year experience in a university center and identified 10 patients with duodenal lymphoma (five localized, five disseminated). Histologic types included diffuse large B-cell in four patients, mucosa-associated lymphoid tumor in three, and Hodgkin, follicular, and unclassified (one each). Treatments included chemotherapy in four patients, radiation therapy (RT) in two patients, Helicobacter pylori treatment in two, and observation in one. Five patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Given these results, implementation of the follow‐up strategy recommended for gastric MALT lymphoma in the current guidelines would appear to be inadequate for patients with duodenal MALT lymphoma 24,25 . Several studies of duodenal MALT lymphoma have shown that H. pylori eradication is effective, either alone or in addition to chemotherapy 8,15,26,27 . By contrast, there are contradictory reports that H. pylori eradication is ineffective for duodenal MALT lymphoma 15,16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Given these results, implementation of the follow‐up strategy recommended for gastric MALT lymphoma in the current guidelines would appear to be inadequate for patients with duodenal MALT lymphoma 24,25 . Several studies of duodenal MALT lymphoma have shown that H. pylori eradication is effective, either alone or in addition to chemotherapy 8,15,26,27 . By contrast, there are contradictory reports that H. pylori eradication is ineffective for duodenal MALT lymphoma 15,16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 307 cases of primary GI non-Hodgkin's lymphoma, 244 cases (80%) had gastric lymphoma and 63 cases (20%) intestinal lymphoma [ 14 ], whereas in another study of 150 GI lymphomas, 105 patients had gastric lymphoma, 27 patients had jejunoileal lymphoma, and only 1 patient had primary duodenal lymphoma [ 15 ]. The literature review of duodenal MALTomas identified only 17 cases reported before 2004 [ 16 ], and only moderately more cases have been reported since [ 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duodenal MALTomas appear similarly at EGD [ 41 ]. A comprehensive literature review revealed that duodenal MALTomas rarely present with no endoscopically apparent lesions [ 16 , 17 , 18 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 30 , 31 , 34 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jednogodišnje pre'ivljavanje pacijenata bilo je 25%, dok je jednogodišnje pre'ivljavanje za nehirurške bilo 10%. 4 U Sato-voj analizi folikularnih duodenalnih limfoma, gdje se analiziraju klini~ko patološke karakteristike 40 pacijenata sa ovim tumorom, zaklju~uje se da folikularni limfom duodenuma ima prelazne karakteristike MALTlimfoma 5 .…”
Section: Diskusijaunclassified